2005
DOI: 10.3171/spi.2005.3.5.0355
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of thoracic outlet syndrome: a randomized trial comparing two operations

Abstract: Object. Various surgical approaches have been proposed for the treatment of thoracic outlet syndrome (TOS). The authors of this study focused on the differences in outcome after supraclavicular neuroplasty of brachial plexus (SNBP [no rib resection]) and transaxillary first rib resection (TFRR) in patients in whom the dominant clinical problem was pain. Methods. Fifty-five patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
43
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(45 citation statements)
references
References 38 publications
0
43
0
2
Order By: Relevance
“…5 Sheth and Campbell reported that the transaxillary approach was superior to the supraclavicular approach in a prospective randomized control trial of 55 patients with painful neurologic TOS. 20 However, a recent Cochrane review concluded that there is insufficient evidence to support any treatment of TOS over another. 21 Our patient demonstrated good short-term improvement following supraclavicular decompression and resection of the cervical rib and pseudoarthrosis.…”
Section: Discussionmentioning
confidence: 99%
“…5 Sheth and Campbell reported that the transaxillary approach was superior to the supraclavicular approach in a prospective randomized control trial of 55 patients with painful neurologic TOS. 20 However, a recent Cochrane review concluded that there is insufficient evidence to support any treatment of TOS over another. 21 Our patient demonstrated good short-term improvement following supraclavicular decompression and resection of the cervical rib and pseudoarthrosis.…”
Section: Discussionmentioning
confidence: 99%
“…The major compressive element in patients with TOS-associated pain appeared to be the first rib. 18 Total resection of the first rib with its periosteum should be preferred in all of these cases with accompanying pathologies such as cervical rib, fibrous ligaments, and scalene muscle. The transaxillary approach provides a good exposure for the resection of cervical ribs, the first rib, and excision of fibrous ligaments and scalene muscle with an excellent cosmetic result.…”
Section: First Rib Resection: Transaxillary Approachmentioning
confidence: 99%
“…On the other hand, superiority of the transaxillary approach for better outcomes compared with supraclavicular approach has been documented (19). This varying knowledge confirms that there is still big room to field of surgical treatment of TOS.…”
mentioning
confidence: 95%
“…Transaxillary approach has a potential of better cosmetic outcome due to the incision site but pointed for higher risk for brachial plexus injury (1). The surgical outcomes comparing 2 common approaches do not show a significant difference (15,16). Both methods may have operative complications including long thoracic nerve injury during dissection of middle scalenus muscle, brachial plexus injury, phrenic nerve injury (17) and Horner syndrome which has been addressed to occur in supraclavicular approach more (17).…”
mentioning
confidence: 98%